2001
DOI: 10.1080/089419301753435693
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Xenogeneic Acellular Collagen Matrix as a Small-Diameter Vascular Graft in Dogs-Preliminary Observations

Abstract: Autogenous veins are the materials of choice for arterial reconstruction. In the absence of autogenous material, prosthetic materials are used. However, vascular prostheses of less than 0.4 cm in diameter have low long-term patency. This study was designed to determine if cells would infiltrate an engineered xenogeneic biomaterial used as a small diameter arterial graft in dogs and, if so, to determine the phenotype of the infiltrating cells. Nine acellular xenogeneic grafts (0.4 cm in diameter, 5 cm long), co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The patency rate obtained during the present study is comparable to those of related studies, that is, 100% patency at 3 months for cryopreserved allografts in a sheep model (10), 87% patency in xenografts treated using a crosslinking technique during 30 days of observation in a sheep-to-dog model (11), and 89% patency for xenogenic acellular collagen matrix grafts (12).…”
Section: Discussionsupporting
confidence: 90%
“…The patency rate obtained during the present study is comparable to those of related studies, that is, 100% patency at 3 months for cryopreserved allografts in a sheep model (10), 87% patency in xenografts treated using a crosslinking technique during 30 days of observation in a sheep-to-dog model (11), and 89% patency for xenogenic acellular collagen matrix grafts (12).…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies on arterial allografts [16–18] and xenografts [14, 1921] have shown that an arterial extracellular matrix may be preserved and seeded with the host's endothelial cells to prevent immunogenic rejection. These processes are advantageous because the graft is available in days rather than weeks or months.…”
Section: Introductionmentioning
confidence: 99%
“…Natural biopolymers, such as collagen and fibrin, support enhanced cellular functions but lack adequate mechanical strength for arterial implantation [Swartz et al, 2005;Yao et al, 2005Yao et al, , 2008Isenberg et al, 2006;Shaikh et al, 2008]. On the other hand, native decellularized tissues such as arteries and small intestine submucosa (SIS) demonstrate sufficient mechanical strength and may provide inherent biological signals to guide tissue repair and remodeling [Huynh et al, 1999;Nemcova et al, 2001;Conklin et al, 2002;Gui et al, 2009;Tottey et al, 2010]. Regardless of the cell source or material, the difficulty in engineering vascular substitutes lies in matching the appropriate mechanical properties of bioactive materials with desirable blood compatibility and immunity characteristics, which are essential for longterm patency [Dahl et al, 2011;Desai et al, 2011].…”
Section: Introductionmentioning
confidence: 99%